Unusual Increased Blood Pool Activity on 68Ga-DOTATATE PET/CT in a Patient With Metastatic Neuroendocrine Disease. (February 2022) - Sharma, Akash; Navaz, Anem J.; Pandey, Mukesh K.; Parent, Ephraim E.
Abstract : Abstract: 68 Ga-DOTATATE is a well-established, positron-emitting, somatostatin receptor–binding radiopharmaceutical. We present an unusual case of transiently increased blood pool uptake of 68 Ga-DOTATATE in a patient with well-differentiated stage IV neuroendocrine tumor, with Ki-67 <2% (WHO grade 1) maintained on lanreotide. During serial 68 Ga-DOTATATE PET/CT examinations, increased blood pool accumulation of presumably unbound 68 Ga was demonstrated, which could impact the Kenning score and lead to a false treatment response assessment.